Characteristics and Effectiveness of Alcohol Website Age Gates Preventing Underage User Access. (24th October 2020) - Barry, Adam E; Primm, Kristin; Russell, Hannah; Russell, Alex M
Abstract: Aims: Examine and evaluate the overall effectiveness of age gates preventing access of underage users to alcohol websites. Methods: Assess the characteristics of digital age gates among the top 25 alcohol brands among American adolescents, including type of age gate employed and resulting actions of repeated access requests indicating the user was under the legal drinking age. Results: All official alcohol brand websites examined included an age gate, requiring either entering one's date of birth (DOB, 91%) or clicking a yes/no box indicating they were of legal drinking age (9%). Only one out of every five alcohol websites blocked futures attempts to gain access after entering a response indicating the user was under the legal drinking age. Users were allowed indefinite attempts to enter a DOB that was of legal drinking age, with the majority of websites subsequently granting access even after multiple underage entries. Conclusions: Alcohol website visitors with minimal arithmetic abilities, such as very young youth, are able to employ 'trial and error' to eventually enter an acceptable legal drinking DOB and gain access. Alcohol brand age gates are weak, at best, and likely an inconsequential barrier that someone with limited math abilities can easily overcome. Abstract : Short Summary: The majority of age gates employed by alcohol websites allow for repeated attempts at entry despite entering underage indications numerous times, allowing visitors with minimal arithmetic abilities, such as very young youth, a 'trial and error' approach to gain access. Alcohol brand age gates represent an inconsequential barrier easily overcome.